A feasible electro-Fenton treatment of landfill leachate diluted by electro-Fenton effluent: Evaluation of operational parameters, effect of dilution ratio and assessment of treatment cost. (June 2022) - Li, Mingran; Zhou, Mengnan; Qin, Xia
Abstract: In recent years, treatment of landfill leachate is becoming a hot issue in the disposal of municipal solid waste. In this study, electro-Fenton (EF) was conducted to dispose landfill leachate pre-treated by membrane bio-reactor (MBR). The optimum operating parameters were evaluated by the orthogonal experiment: U = 5.5 V, t = 50 min, H2 O2 /COD0 = 1.5, H2 O2 /Fe 2+ = 2.5 and pH = 4.0. Average COD removal reached 93.90% at a 95% confidence level and voltage, HRT and H2 O2 /Fe 2+ were found to significantly affect COD removal. Landfill leachate was further diluted by distilled water or EF effluent with different dilution ratio and then followed by EF treatment. With a dilution ratio of EF effluent: landfill leachate = 2:1, electro-Fenton got the best treatment performance, whose COD decreased to 36.2 mg/L, meeting the effluent discharge standard of China. The residual active chlorine species and oxidizing matters in EF effluent improved the effect of following electro-Fenton process. Through analysis of ultraviolet-visible spectrometry (UV–vis) and three-dimensional excitation emission matrix fluorescence spectrometry (3D-EEM), humic acids, ultraviolet fulvic acids, visible fulvic acids in landfill leachate was effectively decomposed and the humification of landfill leachate decreased significantly in this treatment mode. Comparing with other reported works, this treatment obtained high removal efficiency (91.90–93.35%), low energy consumption (3.32–6.24 kWh/kgCOD) and low treatment cost (0.853–1.418 US/m 3 ). This work provided a new perspective in the EF treatment of landfill leachate through diluted by EF effluent with suitable dilution ratio and operating parameters. Graphical abstract: Unlabelled Image Highlights: Landfill leachate diluted by EF effluent had a better degradation in EF process. Landfill leachate achieved effluent discharge standard by this treatment mode. Operation parameters were optimized by the orthogonal experiment. The humification of landfill leachate decreased significantly in this treatment mode. This work exhibited high removal efficiency, low energy consumption and total cost.